Developing a Flexible Platform for Crowdsourcing Historical Weather Records. Issue 3 (3rd July 2019) - Sieber, Renée; Slonosky, Victoria
Abstract: Climatological data exists in historical documents, such as observatory registers, newspapers, ships' logs and private diaries. Using present-day technologies, such as open source repositories and code mashups, and high-resolution digital scanning, software applications can be custom-designed to facilitate transcription of data that otherwise exists solely in paper format. We present a citizen science application for transcribing Canadian weather registers from the late 19th Century. The application is designed to engage citizen scientists with the historical record, respond to archival requirements, and fulfill the needs of the modern climate research community. User centered design allows for an iterative process in which end users – transcribers – are part of the entire cycle of system development. Incorporating users early in the process promises more motivated users and more accurate transcriptions of complex, historical scientific data.